INVESTIGATION OF CRITICAL HEAT FLUX ON ABRADED INCONEL 625 TUBE - Ladislav Suk; Kamil Števanka; Taron Petrosyan; Daniel Vlček (Acta Polytechnica CTU Proceedings, 2020)
Aim of this work was to study flow boiling in an annular channel at low pressure and low flow on a tube with modified surface roughness. The tube with the outer diameter of 9.14 mm and the heated length of 380 mm was made of Inconel 625 and was manually modified using 150 grit sandpaper. The tube was placed in a glass tube with an inner diameter of 14.8 mm. Outlet pressure was set to 120, 200 and 300 kPa with varying mass flow from 400 to 600 kg/(m2.s). A high speed camera was used to record several experiments to fully understand ongoing phenomena. Surface roughness was analysed using a confocal laser microscope and the effects of different mass flux and pressure on the CHF value were observed. Above all, the optimization of the flow parameters was done from the collected data and from the observed behaviour of the experimental loop.